2018
DOI: 10.11005/jbm.2018.25.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Sarcopenia in Female Patients with Osteoporotic Fracture

Abstract: BackgroundWe determined the prevalence of sarcopenia according to fracture site and evaluated the associated risk factors in female patients with osteoporotic fractures.MethodsA total of 108 patients aged 50 years or older with an osteoporotic fracture (hip, spine, or wrist) were enrolled in this retrospective observational study. A diagnosis of sarcopenia was confirmed using whole-body densitometry for skeletal muscle mass measurement. Logistic regression analysis was used to analyze the risk factors for sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…[35,[37][38][39][40][41] Treating nonunions with TPTD could be of great interest mainly because it allows patients to avoid another surgery and autograft associated problems, such as donor site pain or neurovascular injury. [42,43] In addition to its effectiveness in treating nonunion, there were no side effects that occurred in all case reports during the follow-up period. Several animal studies have shown that PTPD by dual mechanism of action, influencing both bone formation activity and bone resorption.…”
Section: Can Tptd Be An Alternative For Nonunion?mentioning
confidence: 87%
“…[35,[37][38][39][40][41] Treating nonunions with TPTD could be of great interest mainly because it allows patients to avoid another surgery and autograft associated problems, such as donor site pain or neurovascular injury. [42,43] In addition to its effectiveness in treating nonunion, there were no side effects that occurred in all case reports during the follow-up period. Several animal studies have shown that PTPD by dual mechanism of action, influencing both bone formation activity and bone resorption.…”
Section: Can Tptd Be An Alternative For Nonunion?mentioning
confidence: 87%
“…Although muscle atrophy and bone loss may occur simultaneously, bone fractures are often preceded by loss of muscle mass and strength. The endocrine functions of skeletal muscles [ 471 , 472 , 473 , 474 , 475 , 476 , 477 ], the tight bidirectional (patho) physiological muscle-bone cross-talk [ 142 , 209 , 478 , 479 , 480 , 481 , 482 , 483 , 484 , 485 , 486 , 487 , 488 , 489 , 490 , 491 , 492 ], and their shared genetics [ 493 , 494 , 495 , 496 ] are well recognized. Not surprisingly, RFs for OP and falls often coexist (up to 63% in patients with HF [ 497 ]).…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Sarcopenia, the degenerative decrease of skeletal muscle mass (0.5%–1% loss per year after the age of 50) has been investigated as a new risk factor for fracture. [ 5 6 7 8 ] Regardless of bone density, sarcopenia appears to be an independent risk factor for fragility fractures leading to a condition known as sarco-osteoporosis. [ 7 ] With respect to DRF, Roh et al[ 6 ] reported a higher prevalence of sarcopenia in patients with DRF compared to age- and sex-matched controls.…”
Section: Introductionmentioning
confidence: 99%